2020
DOI: 10.22270/jddt.v10i6.4456
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, Practice and Associated Factors of Adult Population towards Blood Donation in Jigjiga Town, Somali Region, Ethiopia

Abstract: Background: Secure supply of safe blood components, based on voluntary, non-remunerated blood donation, is an important national goal to prevent blood shortages. Nowadays, in many low- and middle-income countries, blood supply is critically inadequate. Sub-Saharan Africa, which has the highest maternal mortality rate in the world of 510 deaths per 100000 live births, also has the lowest blood donation rates. The donated blood plays a big role during surgery, accident, delivery cases and in many bleeding cases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Previous research has shown that blood donation behavior is associated with various factors, including socioeconomic status and education 2–12 . Specifically, individuals with higher levels of education and income tend to have a higher likelihood of donating blood.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous research has shown that blood donation behavior is associated with various factors, including socioeconomic status and education 2–12 . Specifically, individuals with higher levels of education and income tend to have a higher likelihood of donating blood.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that blood donation behavior is associated with socioeconomic factors such as income and education. These findings were mainly based on surveys and questionnaires 8–15 . In contrast, the current study aims to investigate the same relationship using correlation and regression analysis based on a large database of blood donation records.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations